(untitled) (Journal of Organizational Psychology, 2021)
Consulting firms that specialize in industrial-organizational (I-O) psychology have begun using social media to promote products and services, yet little research has been done on their attempts to market the field. 382 Tweets were collected and analyzed from 16 human capital consulting firm Twitter accounts. Likes, comments, and retweets were also collected. Analyses revealed that medium-sized firms had higher engagement scores than both boutique and large firms. Text analyses revealed that boutique firms used more positive language than large firms. Content that was coded as entertaining was the largest driver of social media engagement. We recommend that consulting firms use more humor and relational language in their posts to draw greater levels of engagement. Future research should expand to other social media platforms (i.e., Facebook, Instagram, TikTok).